A105 RAPID INTERDISCIPLINARY IBD CLINIC RESULTS IN TIMELY IBD WAIT TIMES, IMPROVED PATIENT SATISFACTION & PATIENT REPORTED OUTCOMES. (4th March 2021) - Buffone, E; Jogendran, R; Broni, E; O'Connor, K; Panayotova, K; Kennedy, E; Steiman, A; Maxwell, C; Alavi, A; Weizman, A V; Huang, V W
Abstract: Background: Inflammatory Bowel Disease (IBD) patients often have disease flares and extraintestinal manifestations such as rashes, arthralgias & perianal fistulas that require timely assessments. We implemented a Rapid Interdisciplinary IBD program at Mount Sinai Hospital with expedited consultation by an IBD specialist and referral with clinical need to collaborative colorectal surgeon, dermatologist, rheumatologist, and/or high-risk obstetrician. The RAPID program includes an online IBD Dashboard for patients to respond to questionnaires which is closely monitored 90 days post-enrolment by the IBD nurse. Aims: To assess the implementation of an Interdisciplinary IBD Clinic & online IBD Dashboard monitoring system on the ability to increase patient satisfaction regarding their IBD care. Methods: Upon consent into the RAPID IBD program, patients are enrolled to the IBD Dashboard and complete a Patient Satisfaction (CACHE) questionnaire at baseline, 3, 6, 12 months follow up and clinical disease activity scores at baseline, 1, 2, 3 months post enrollment; the Modified Harvey Bradshaw Index (mHBI) for Crohn's disease (CD); partial Mayo score and Simple Clinical Colitis Activity Index (SCCAI) for ulcerative colitis (UC) and IBD unclassified (IBDU) patients. Results were compared pre/post enrollment with changes in median and interquartile ranges (IQR). Results: 109 patients were referred to RAPID, 88 (49 CD, 33 UC, 6 IBDU) enrolled & 62 consented to IBD Dashboard monitoring. Of those enrolled, 40 patients were referred based on flaring of clinical scores, 23 with potential flare or complication, 17 with acute extraintestinal manifestations, 4 pregnant and 4 with perianal disease. Median 4 (2–7) days to first GI IBD clinic. 15 patients were referred to dermatology, 12 to colorectal surgery, 8 to rheumatology and 3 to obstetrics. 6 patients visited the ER within the first 90 days after enrollment, with 1 (1–2) ER visits. Patient satisfaction improved from baseline 73.5% (68.4%-77.4%) (n=53) to 82.3% (75.5% - 84.0%) at 3 months (n=28). Clinical responses were seen post enrollment with a decrease in mHBI of 3.0 at 2 months, 1.5 on the 6-point Mayo (SF + RB) at 1 & 3 months and patient defined significant improvement in SCCAI greater than 1.5 after 1 month. Conclusions: Preliminary results with RAPID IBD program demonstrate a short time to be seen by an IBD specialist, improvement in patient satisfaction and clinical responses in mHBI, pMayo and SCCAI scores 1–3 months post enrollment. Funding Agencies: AMO